2017
DOI: 10.1186/s12913-017-2157-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of interprofessional collaboration of general practitioners and community pharmacists - a qualitative study

Abstract: BackgroundDespite numerous evidences for the positive effect of community pharmacists on health care, interprofessional collaboration of pharmacists and general practitioners is very often limited. Though highly trained, pharmacists remain an underutilised resource in primary health care in most western countries. This qualitative study aims at investigating pharmacists’ and general practitioners’ views on barriers to interprofessional collaboration in the German health care system.MethodsA total of 13 narrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 21 publications
3
73
0
2
Order By: Relevance
“…Professional boundaries were commonly identified as impeding collaboration between GPs and CPs (Bradley et al., ; Dey, de Vries, & Bosnic‐Anticevich, ; Dinnie, Bond, & Watson, ; Howard et al., ; Hughes & McCann, ; Kelly et al., ; Lalonde et al., ; Laubscher, Evans, Blackburn, Taylor, & McKay, ; Legault et al., ; Löffler et al., ; Maidment et al., ; Moore, Kennedy, & McCarthy, ; Pojskic et al., ; Pottie et al., ; Rieck & Pettigrew, ; Rieck, ; Rubio‐Valera et al., ; Sake, Wong, Bartlett, & Saini, ; Saw et al., ; Tan, Stewart, Elliott, & George, , ; Van, Costa, Mitchell, Abbott, & Krass, , , ; Van, Krass, & Mitchell, ; Van, Mitchell, & Krass, ; Varela et al., ; Weissenborn, Haefeli, Peters‐Klimm, & Seidling, ; Wustmann, Haase‐Strey, Kubiak, & Ritter, ; Zillich, McDonough, Carter, & Doucette, ). Professionals’ previous experience with collaboration and a lack of clarity regarding the roles and responsibilities of the GPs and CPs were the most common issues; followed by attitudes, feelings, hierarchy and power, and trust and respect.…”
Section: Resultsmentioning
confidence: 99%
“…Professional boundaries were commonly identified as impeding collaboration between GPs and CPs (Bradley et al., ; Dey, de Vries, & Bosnic‐Anticevich, ; Dinnie, Bond, & Watson, ; Howard et al., ; Hughes & McCann, ; Kelly et al., ; Lalonde et al., ; Laubscher, Evans, Blackburn, Taylor, & McKay, ; Legault et al., ; Löffler et al., ; Maidment et al., ; Moore, Kennedy, & McCarthy, ; Pojskic et al., ; Pottie et al., ; Rieck & Pettigrew, ; Rieck, ; Rubio‐Valera et al., ; Sake, Wong, Bartlett, & Saini, ; Saw et al., ; Tan, Stewart, Elliott, & George, , ; Van, Costa, Mitchell, Abbott, & Krass, , , ; Van, Krass, & Mitchell, ; Van, Mitchell, & Krass, ; Varela et al., ; Weissenborn, Haefeli, Peters‐Klimm, & Seidling, ; Wustmann, Haase‐Strey, Kubiak, & Ritter, ; Zillich, McDonough, Carter, & Doucette, ). Professionals’ previous experience with collaboration and a lack of clarity regarding the roles and responsibilities of the GPs and CPs were the most common issues; followed by attitudes, feelings, hierarchy and power, and trust and respect.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a qualitative study of Australian GPs showed that most did not favour pharmacists’ provision of screening services, as they believed screening to be the role of the GP and lacked confidence in the accuracy of screening tests and pharmacists’ competence . These findings suggest that any pharmacy‐based screening services, even with a robust in‐pharmacy protocol, are likely to have a low success rate unless there are close working relationships between community pharmacists and GPs . More specifically, there is a need to develop an innovative referral pathway, which can ensure that patients who have undergone screening at community pharmacies are subjected to further investigation during their routine visit to the GP …”
Section: Discussionmentioning
confidence: 99%
“…27 These findings suggest that any pharmacy-based screening services, even with a robust in-pharmacy protocol, are likely to have a low success rate unless there are close working relationships between community pharmacists and GPs. 28,29 More specifically, there is a need to develop an innovative referral pathway, which can ensure that patients who have undergone screening at community pharmacies are subjected to further investigation during their routine visit to the GP. 27,29 A distinctive aspect of our study, compared with other pharmacy-based screening studies, was the availability of participant pathology results.…”
Section: Discussionmentioning
confidence: 99%
“…CPs are seen to be in an ideal position to take on the routine management of long‐term conditions, and there is evidence that they can do this . However, establishing collaborative relationships between general practice and community pharmacy has proved difficult . Poor integration of CPs on primary care teams may be one reason why the CPs’ clinical role is not more developed.…”
Section: Introductionmentioning
confidence: 99%
“…[3] However, establishing collaborative relationships between general practice and community pharmacy has proved difficult. [4] Poor integration of CPs on primary care teams may be one reason why the CPs' clinical role is not more developed.…”
Section: Introductionmentioning
confidence: 99%